Risks predicting prolonged hospital discharge boarding in a regional acute care hospital - Sajid A. Shaikh; Richard D. Robinson; Radhika Cheeti; Shyamanand Rath; Chad D. Cowden; Frank Rosinia; Nestor R. Zenarosa; Hao Wang (BMC, 2018)
Abstract Background Prolonged hospital discharge boarding can impact patient flow resulting in upstream Emergency Department crowding. We aim to determine the risks predicting prolonged hospital discharge boarding and their direct and indirect effects on patient flow. Methods Retrospective review of a single hospital discharge database was conducted. Variables including type of disposition, disposition boarding time, case management consultation, discharge medications prescriptions, severity of illness, and patient homeless status were analyzed in a multivariate logistic regression model. Hospital charges, potential savings of hospital bed hours, and whether detailed discharge instructions provided adequate explanations to patients were also analyzed. Results A total of 11,527 admissions was entered into final analysis. The median discharge boarding time was approximately 2 h. Adjusted Odds Ratio (AOR) of patients transferring to other hospitals was 7.45 (95% CI 5.35-10.37), to court or law enforcement custody was 2.51 (95% CI 1.84-3.42), and to a skilled nursing facility was 2.48 (95% CI 2.10-2.93). AOR was 0.57 (95% CI 0.47-0.71) if the disposition order was placed during normal office hours (0800-1700). AOR of early case management consultation was 1.52 (95% CI 1.37-1.68) versus 1.73 (95% CI 1.03-2.89) for late consultation. Eighty-eight percent of patients experiencing discharge boarding times within 2 h of disposition expressed positive responses when questioned about the quality of explanations of discharge instructions and follow-up plans based on satisfaction surveys. Similar results (86% positive response) were noted among patients whose discharge boarding times were prolonged (> 2 h, p = 0.44). An average charge of $6/bed/h was noted in all hospital discharges. Maximizing early discharge boarding (≤ 2 h) would have resulted in 16,376 hospital bed hours saved thereby averting $98,256.00 in unnecessary dwell time charges in this study population alone. Conclusion Type of disposition, case management timely consultation, and disposition to discharge dwell time affect boarding and patient flow in a tertiary acute care hospital. Efficiency of the discharge process did not affect patient satisfaction relative to the perceived quality of discharge instruction and follow-up plan explanations. Prolonged disposition to discharge intervals result in unnecessary hospital bed occupancy thereby negatively impacting hospital finances while delivering no direct benefit to patients.